"Evaluacion de la estrategia de negocios de la empresa importadora Alonso e incidencia en el desarrollo empresarial del cantón El Empalme año 2013 - Zavala Mendoza, Lilia María (2013)
Customer satisfaction is an essential component to increase the competitiveness of the business sector, for it is necessary to evaluate business strategies because through this we can establish whether the activities successful. 58% of the surveyed population has knowledge about the company's business structure Importadora Alonzo, echoing primarily on business strategy The data obtained in our research, we show that the company has a good publicity in the village, which is very important factor in recognizing Importadora Alonzo. The 44% of respondents expressed, due to the importance of the supply company that has the desire and the will to re-make a new purchase. In interview with the manager of the company, it said in essence known business strategies and values that enable the strengthening of human talent and marketing company. Alonzo as determined Importer is monitoring the competition for customers sends them ghosts, not known to them. These observations are oriented towards brands, prices, terms, credits, among others. We recommend the following strategies: customer loyalty, product diversification, market diversification, compete on costs, compete on differentiation, and focus on a specific market segment.